2013
DOI: 10.1038/srep01812
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evolution of human adenoviruses

Abstract: The recent emergence of highly virulent human adenoviruses (HAdVs) with new tissue tropisms underscores the need to determine their ontogeny. Here we report complete high quality genome sequences and analyses for all the previously unsequenced HAdV serotypes (n = 20) within HAdV species D. Analysis of nucleotide sequence variability for these in conjunction with another 40 HAdV prototypes, comprising all seven HAdV species, confirmed the uniquely hypervariable regions within species. The mutation rate among HA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
305
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(319 citation statements)
references
References 52 publications
8
305
0
6
Order By: Relevance
“…Adenovirus predominantly infects epithelial cells of the respiratory and gastrointestinal tracts, and conjunctiva (Robinson et al, 2013). The species C human adenoviruses (HAdV-C2 and -C5) are widespread, persist in adenoid tissue and are lifethreatening to immune-compromised individuals (Lion, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus predominantly infects epithelial cells of the respiratory and gastrointestinal tracts, and conjunctiva (Robinson et al, 2013). The species C human adenoviruses (HAdV-C2 and -C5) are widespread, persist in adenoid tissue and are lifethreatening to immune-compromised individuals (Lion, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the typing can be done through PCR amplification and sequencing of the hexon, penton, and fiber genes. The hexon gene sequence analysis has widely been used for the classification of adenovirus types; however, sequence analysis of the fiber gene has also been incorporated to determine the recombination events in the adenovirus genotype (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Further evaluation of our phylogenetic and recombination analysis data (Table 1 and Figure 1) revealed that in addition to the already mentioned types, several additional types appear to have contributed to the final composition of the HAdV-84 genome, through multiple recombination events. Recombination is one of the major driving forces in HAdV evolution (Gonzalez et al, 2015;Robinson et al, 2013). The penton base's variable loop is most similar to that of HAdV-8, while the remaining penton base backbone is more similar to HAdV-43.…”
mentioning
confidence: 99%